Análise de práticas de economia circular para destinação de pás de turbinas eólicas em final de vida - Centoamore, Plinio (2020)
Wind farms exponential growth will generate a huge amount of wind turbine blades available for disposal. This fact will be due to the life span perspective on service of a wind turbine blade, which is design to work under normal conditions to last about 20-25 years. The current situation arises questions in terms of guarantee a sustainable destination for wind turbine blades, considering their large dimensions together with huge amounts of available parts to be disposal. For this purpose, the study aim to analyze alternatives on destinations for such components that reached theirs end of service life, considering the concepts of a Circular Economy, adopting an orientation towards blades materials components circularity. The potential alternatives shown at literature are still in processes development phase. Some of these alternatives do not demonstrate yet enough consistency to provide a sustainable way to disposal and, at the same time represent an economic gain for the society as such. These possibilities are spread out on several academic studies, having every one, a diverse emphasis for each pathway, so much as reconfiguration for a different application than the original one, throughout recycling processes of materials components, or even landfilling or incineration. The utilized research method was an analysis from experts, which belongs to wind energy market. Using this framework, and combining such possibilities in the same text, this research presents alternatives for blades disposal to those experts, and listened to them about this issue. For the Academy, having a single text containing those available alternatives can be helpful, and, for market could help to take right decisions. For the society as a whole, it will bring an environmental consciousness. Results shows possible destinations, difficulties reported on proper disposal of blades and appropriate actions in terms of processes developments for blades destinations. Debate responsibilities and the hole of official agencies related to this issue. Maintain a focus on concerns that belongs to this business, searching for attitudes environmentally sustainable, combining such activity with a positive financial result.